Chaos-Based Simultaneous Compression and Encryption for Hadoop - Zakaria, Mohd Nordin (2017)
Data compression and encryption are key components of commonly deployed platforms such as Hadoop. Numerous data compression and encryption tools are presently available on such platforms and the tools are characteristically applied in sequence, i.e., compression followed by encryption or encryption followed by compression.